Institutional environment and bank capital decisions: Evidence from developed countries - Liu, Huahui (2022)
We investigate the effect of governance on bank regulatory capital ratios. Using a sample of 374 commercial banks in 14 countries over the 2014 – 2020 period, we find that banks in countries with better institutional environment maintain lower regulatory capital ratios. We also find that small and liquid banks with good quality assets have higher regulatory capital ratios. Our findings contribute to the capital structure literature and put forward several suggestions for bank managers and policymakers.